'We Don't Need No Thought Control' – Rob Gray's Fight Against 'Indoctrination' in Accounting Education. (1st September 2020) - Ferguson, John
ABSTRACT: I have written about Rob before – about his colossal influence on social and environmental accounting research and practice and his immense contribution to accounting academia more broadly. Not only did Rob establish the Centre for Social and Environmental Accounting Research (CSEAR) and Social and Environmental Accountability Journal (SEAJ), but he was instrumental in establishing the British Accounting and Finance Association (BAFA) and The British Accounting Review (BAR). For these reasons alone, there are probably thousands of accounting scholars across the world who have benefited enormously from Rob's trailblazing achievements. In this contribution, I want to remember Rob for another significant aspect of his scholarship. More specifically, I want to remember Rob as an inspirational accounting educator – as someone who cared deeply about his students, his subject and his profession.